2021
DOI: 10.3389/fevo.2021.733062
|View full text |Cite
|
Sign up to set email alerts
|

Night Capture of Roosting Cave Birds by Neanderthals: An Actualistic Approach

Abstract: Evidence is accumulating on the regular and systematic Neanderthal exploitation of birds. However, the motivations, mechanisms, and circumstances underlying this behavior remains little explored despite their potential implications on Neanderthal ecology and capabilities. Fossil remains of choughs (Pyrrhocorax, Corvidae) are among the most abundant in cave sites with Mousterian technology. We reviewed the evidence showing that Neanderthals processed choughs for food, and confirmed that it occurred frequently o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…To gain support to our hypothesis that the slate plaques and some related objects were children dolls or toys of little ritual value that may have been crafted for young people and not necessarily by experienced artisans of the community, we establish a comparison with owls as seen by contemporary children, taking therefore an actualistic approach (see, e.g., Blanco et al 28 ). We assume that the differences in the craftsmanship of the plaques may well result from differences in the technical skill of the engravers associated to age and experience, as we see…”
Section: Methodsmentioning
confidence: 99%
“…To gain support to our hypothesis that the slate plaques and some related objects were children dolls or toys of little ritual value that may have been crafted for young people and not necessarily by experienced artisans of the community, we establish a comparison with owls as seen by contemporary children, taking therefore an actualistic approach (see, e.g., Blanco et al 28 ). We assume that the differences in the craftsmanship of the plaques may well result from differences in the technical skill of the engravers associated to age and experience, as we see…”
Section: Methodsmentioning
confidence: 99%
“…The large presence of choughs (Pyrrhocorax pyrrhocorax and Pyrrhocorax graculus) in avian assemblages has been commonly attributed to chough nesting and roosting behaviour in rocky cavities. Very recently it has been observed that this pattern of overabundance does not occur with other rock dweller species, and is only observed in caves with evidence of human presence, and as such it has been proposed that these birds may have been hunted since Neanderthal times [77]. Most avian bones recorded correspond to diurnal species, but there are also some nocturnal raptors.…”
Section: Birdsmentioning
confidence: 97%
“…Hunting, tools, and clothing. Recent publications in this area include the results of an actualistic study suggesting Neandertals captured birds (specifically) at night (Blanco et al 2021 On: Sat, 01 Jun 2024 10:18:49 also Finlayson 2019). Other studies show that Neandertals employed ambush hunting rather than persistence hunting when pursuing prey, which is hypothesized to have been a crucial difference between them and modern humans, giving the latter a competitive edge (Stewart et al 2019).…”
Section: Diet and Sense Of Smellmentioning
confidence: 99%